Loss of Function of the E1-Like-b Gene Associates With Early Flowering Under Long-Day Conditions in Soybean - Zhu, Jianghui; Takeshima, Ryoma; Harigai, Kohei; Xu, Meilan; Kong, Fanjiang; Liu, Baohui; Kanazawa, Akira; Yamada, Tetsuya; Abe, Jun (Frontiers in Plant Science, 2019)
Photoperiod response of flowering determines plant adaptation to different latitudes. Soybean, a short-day plant, has gained the ability to flower under long-day conditions during the growing season at higher latitudes, mainly through dysfunction of phytochrome A genes (E3 and E4) and the floral repressor E1. In this study, we identified a novel molecular genetic basis of photoperiod insensitivity in Far-eastern Russian soybean cultivars. By testcrossing these cultivars with a Canadian cultivar Harosoy near-isogenic line for a recessive e3 allele, followed by association tests and fine mapping, we determined that the insensitivity was inherited as a single recessive gene located in an 842-kb interval in the pericentromeric region of chromosome 4, where E1-Like b (E1Lb), a homoeologue of E1, is located. Sequencing analysis detected a single-nucleotide deletion in the coding sequence of insensitive cultivars, which generated a premature stop codon. Comparative analyses of near-isogenic lines indicated that the loss-of-function allele (designated e1lb) upregulated the expression of soybean FLOWERING LOCUS T (FT) orthologues, FT2a and FT5a, to promote flowering under long-day conditions in both the e3/E4 and E3/E4 genetic backgrounds. The e1lb allele completely canceled the inhibitory effect of far-red light–enriched long-day conditions, which is mediated by E4, but not that of red-light–enriched long-day conditions, which is mediated by E3. These findings suggest that E1Lb retards flowering under long-day conditions independently of E1 by repressing the expression of FT2a and FT5a. This loss-of-function allele can be used as a new resource in breeding of photoperiod-insensitive cultivars, and may improve our understanding of the function of the E1 family genes in the photoperiod responses of flowering in soybean.